Pengaruh Literasi Keuangan Terhadap Perilaku Pengelolaan Keuangan Masyarakat di Desa Langkura Kecamatan Turatea Kabupaten Janeponto - Lisa Herianti; Anwar Ramli; Anwar (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
Financial literacy is closely related to financial management, where the higher the financial literacy, the higher the financial management. Financial management itself is a form of managing one's finances both for the present and the future. The aim of this research is to determine the influence of financial literacy on community financial management behavior in Langkura Village, Turatea District. This research uses a quantitative type of research with a quantitative descriptive approach and is also included in explanatory research. The population used was 2786 with a sample of 350 and the sampling technique used non-probability sampling. Data analysis used in this research uses descriptive statistical analysis, inferential statistical analysis and hypothesis testing. The results of this research show that first, the financial literacy level of the community in Langkura Village, Turatea District is in the very good category. Second, the financial behavior of the community in Langkura Village, Turatea District is also in the very good category. Third, the results of hypothesis testing carried out by researchers show that financial literacy has a partial and significant effect on the financial behavior of people in Langkura Village, Turatea District. Therefore, the level of people's knowledge and ability to manage personal and family finances well can provide direction to someone to manage their finances well too.